Five New Cytotoxic Metabolites from the Marine Fungus Neosartorya pseudofischeri - Wen-Jian Lan; Sheng-Jiao Fu; Meng-Yang Xu; Wan-Ling Liang; Chi-Keung Lam; Guo-Hua Zhong; Jun Xu; De-Po Yang; Hou-Jin Li (Marine Drugs, 2016)
The marine fungus Neosartorya pseudofischeri was isolated from Acanthaster planci from the South China Sea. In a preliminary bioactivity screening, the crude methanol extract of the fungal mycelia showed significant inhibitory activity against the Sf9 cell line from the fall armyworm Spodoptera frugiperda. Five novel compounds, including 5-olefin phenylpyropene A (1), 13-dehydroxylpyripyropene A (4), deacetylsesquiterpene (7), 5-formyl-6-hydroxy-8-isopropyl-2- naphthoic acid (9) and 6,8-dihydroxy-3-((1E,3E)-penta-1,3-dien-1-yl)isochroman-1-one (10), together with eleven known compounds, phenylpyropene A (2) and C (3), pyripyropene A (5), 7-deacetylpyripyropene A (6), (1S,2R,4aR,5R,8R,8aR)-1,8a-dihydroxy-2-acetoxy-3,8-dimethyl-5- (prop-1-en-2-yl)-1,2,4a, 5,6,7,8,8a-octahydronaphthalene (8), isochaetominine C (11), trichodermamide A (12), indolyl-3-acetic acid methyl ester (13), 1-acetyl-β-carboline (14), 1,2,3,4-tetrahydro-6-hydroxyl-2-methyl-l,3,4-trioxopyrazino[l,2-a]-indole (15) and fumiquinazoline F (16), were obtained. The structures of these compounds were determined mainly by MS and NMR data. The absolute configuration of 9 was assigned by the single-crystal X-ray diffraction studies. Compounds 1–11 and 15 showed significant cytotoxicity against the Sf9 cells from S. frugiperda.